We Go on a School Bus - Mattern, Joanne, 1963- (Egremont, MA : Red Chair Press, 2020)
"What to expect from a trip on a school bus"--Provided by publisher.
Includes index
Keywords: Transportation -- Juvenile literature; School buses -- Juvenile literature